232 HYBRID MINIMALLY INVASIVE ESOPHAGECTOMY FOR ESOPHAGEAL CANCER: FIVE-YEAR SURVIVAL RESULTS OF THE MIRO TRIAL. (14th September 2020) - Nuytens, F; Dabakuyo-Yonli, S; Meunier, B; Pezet, D; Collet, D; DJourno, X; Brigand, C; Perniceni, T; Carrère, N; Mabrut, J; Msika, S; Peschaud, F; et al.
Abstract:  : Multiple randomized controlled trials have demonstrated the short term benefits of (hybrid) minimally invasive esophagectomy (MIE) over open esophagectomy. Data regarding long term results are more conflicting with similar or even better results in the MIE arm. In this follow-up study of the MIRO-trial we evaluated the long-term 5-year outcomes including overall survival (OS), disease-free survival (DFS) as well as the pattern of disease recurrence, along with evaluation of potential prognostic factors affecting these outcomes. Methods: From October 2009 till April 2012, we conducted a multicentre, open-label, prospective, randomized, controlled trial including patients who were diagnosed with thoracic esophageal cancer and eligible for curative surgical resection (Ivor-Lewis procedure). Patients were randomized between hybrid minimally invasive esophagectomy and open esophagectomy. The primary end-point of the initial MIRO trial was major intra- and postoperative complication (Clavien-Dindo ≥2) within 30 days after surgery. The primary end-points of this follow-up study were OS and DFS. Additional secondary end points were defined as site of disease recurrence and potential prognostic or mediating factors associated with DFS and OS. Results: 207 patients underwent randomization. The median follow-up was 58, 2 (95% CI, 56, 5– 63, 8) months. The 5y OS was 59% (95% CI, 48–68) and 47% (95% CI, 37–57) in the hybrid- and open-procedure group respectively (HR, 0, 71, 95% CI, 0, 48-1, 06). The 5y DFS was 52% (95% CI, 42–61) in the hybrid-procedure group vs. 44% (95%CI, 34–53) in the open-procedure group. (HR 0.81 (95% CI, 0, 55-1, 17). There was no significant difference in recurrence rate (p = 0.519) or -location (p = 0.692) between groups. In a multivariate analysis, major postoperative and pulmonary complications were identified as prognostic factors of impaired OS (p < 0.0001;p = 0.005) and DFS (p = 0.002;p = 0.006). Conclusion: Besides a significant reduction in postoperative overall and pulmonary complication rate, minimally invasive (hybrid) esophagectomy offers long-term oncological results that are at least equivalent to open esophagectomy. Postoperative and pulmonary complications are independent prognostic factors for impaired overall- and disease-free survival, providing additional proof that minimally invasive esophagectomy could even be associated with better long-term oncological results compared to open esophagectomy mediated by a reduction in postoperative complications.